Translation Shifts in the Short Story 'The Gift of the Magi': Analyzing Linguistic and Cultural Adaptations in Meaning - Putu Wulan Prabhaswari; A.A. Sg. Shanti Sari Dewi; Gek Wulan Novi Utami (Pusat riset dan Inovasi Nasional, 2025)
This study examines the translation shifts in the short story The Gift of the Magi, which was translated from English to Indonesian under the title Pemberian Sang Majus by Maggie Tiojakin. The purpose of this study is to identify and analyze the types of translation shifts present in the short story. Data collection was carried out using the documentation method, with the data analyzed based on Catford's translation shift theory using a descriptive qualitative approach. The findings of this study reveal that several types of translation shifts are evident in the short story. These include shifts of level, shifts of structure, shifts of unit, and shifts of intra-system. Shifts of level occur when an item in the source language at one linguistic level has an equivalent in the target language at a different level. For example, a phrase in the source language may be translated as a word or clause in the target language. Shifts of structure refer to differences in grammatical structures between the source and target languages, such as changes in sentence construction or word order to ensure fluency in the translation.